2009
DOI: 10.1016/j.mce.2009.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin increases GnRH mRNA expression and secretion in GnRH secreting neuronal cell lines

Abstract: Kisspeptins, and their G-protein coupled receptor 54 (GPR54), are key components in the regulation of gonadotropin-releasing hormone (GnRH) secretion in humans and other mammals. Several studies demonstrate that the central or systemic administration of kisspeptin increases GnRH and gonadotropin secretion in both prepubertal and adult animals; however, the cellular targets and intracellular mechanisms of action in the central reproductive axis are unclear. In this study, we documented the presence of GPR54 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 71 publications
(95 reference statements)
7
86
0
1
Order By: Relevance
“…Kisspeptin was demonstrated to increase the intracellular calcium concentration [Ca 2C ] i in isolated GnRH neurons (Kroll et al 2011) as well as in hypothalamic GT1-7 immortalized cell lines (Ozcan et al 2011). Furthermore, GnRH secretion was increased in kisspeptin-activated GT1-7 cells (Jacobi et al 2007, Novaira et al 2009, Tonsfeldt et al 2011. Taken together, these findings implicate an important role for kisspeptin/GPR54 for the regulation of sexual maturation and the development of the reproductive system.…”
Section: Introductionmentioning
confidence: 86%
“…Kisspeptin was demonstrated to increase the intracellular calcium concentration [Ca 2C ] i in isolated GnRH neurons (Kroll et al 2011) as well as in hypothalamic GT1-7 immortalized cell lines (Ozcan et al 2011). Furthermore, GnRH secretion was increased in kisspeptin-activated GT1-7 cells (Jacobi et al 2007, Novaira et al 2009, Tonsfeldt et al 2011. Taken together, these findings implicate an important role for kisspeptin/GPR54 for the regulation of sexual maturation and the development of the reproductive system.…”
Section: Introductionmentioning
confidence: 86%
“…To gain further insight into the downstream pathways used by kisspeptin-GPR54 signaling to promote nNOS phosphorylation in preoptic neurons, we investigated whether kisspeptin activation of its cognate receptor is coupled with the activation of the phosphatidylinositol-3 kinase (PI3K)/AKT signaling pathway, which is thought to mediate the phosphorylation of Ser1412 in nNOS (Rameau et al, 2007) and has been shown to be stimulated by GPR54 signaling (Stathatos et al, 2005;Novaira et al, 2009). We also explored the putative activation of the ERK1/2 signaling pathway, which has been shown to be stimulated by the activation of GPR54 (Castellano et al, 2006).…”
Section: Kisspeptin Promotes Nnos Phosphorylation Via the Activation mentioning
confidence: 99%
“…The evidence related to the stimulatory effects of kisspeptins on GnRH neurons has been provided mainly from animal studies [7]. They have shown increased expression of GnRH mRNA by GnRH neurons after kisspeptin exposure [40,41]. Likewise, it has been shown that kisspeptins can evoke an increased firing rate of GnRH neurons as measured by voltage recordings in hypothalamic slices from mice [42][43][44][45], stimulate the release of GnRH in hypothalamus explants [46,47], and cause a dramatic increase in GnRH in the CSF of sheep [48].…”
Section: Physiological Role Of Kisspeptins In Modulating Gnrh Secretionmentioning
confidence: 99%